78=-2m+6+m

Simple and best practice solution for 78=-2m+6+m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 78=-2m+6+m equation:


Simplifying
78 = -2m + 6 + m

Reorder the terms:
78 = 6 + -2m + m

Combine like terms: -2m + m = -1m
78 = 6 + -1m

Solving
78 = 6 + -1m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add 'm' to each side of the equation.
78 + m = 6 + -1m + m

Combine like terms: -1m + m = 0
78 + m = 6 + 0
78 + m = 6

Add '-78' to each side of the equation.
78 + -78 + m = 6 + -78

Combine like terms: 78 + -78 = 0
0 + m = 6 + -78
m = 6 + -78

Combine like terms: 6 + -78 = -72
m = -72

Simplifying
m = -72

See similar equations:

| 2(3x-4)=5x-6 | | 3x-1=-8+8x | | 3x-33=15 | | 7x+25=235 | | 122+32+n=180 | | -1x+4=8.0 | | =19-15(-9+17k) | | 8-81+-2n=-75 | | x+3=-x+7 | | -5x+10=2x+31 | | 7+25x=235 | | 6=-x+4x | | 3x+5x-10=10x+5x+10-20 | | 1200-870-30x=11 | | 13x^2y^2+39x^4y= | | 8b^2+16b=0 | | 1.5f=8 | | 1.5f= | | 25x+7=235 | | 10a+-7+9=-26 | | -2.5(c+6)=3g-6g | | 50+0.10=0.18m | | -6-8(4n+8)=2(1-4n) | | -2x+15=20 | | 2x^4-5x^3-3x^2+x=0 | | (7+i)(6-9i)= | | a-2+5a=22 | | 11xy^6+77x^3y^4= | | -3x^2+42=0 | | 12+7b=6b | | 4.2=7Z+2.8 | | 4d-11=2b+7 |

Equations solver categories